Structural-methodical model of computer program for control of theoretical knowledge of cadets - V. V. Bulgakov (Открытое образование (Москва))
The aim of the study is to develop a structural and methodological model of training, testing and control of theoretical knowledge of students, taking into account the peculiarities of the educational process in the departmental University of the Ministry of emergency situations of Russia. The review of computer programs used in the educational process showed that the number of software products independently created in educational organizations, which have a wide range of functions for the preparation and control of theoretical knowledge, are quite rare. Basically, readymade computer programs are used, which are universal and are intended for wide application, without taking into account the specifics of Universities.Research and development of structural and methodological model was carried out with the use of theoretical analysis of the provisions of pedagogy on the problems of control, evaluation and analysis of the level of theoretical knowledge, methods of theory of algorithms and decision-making, methods of synthesis and analysis of information processes. The developed structural and methodological model of training organization, testing and control of theoretical knowledge of cadets is based on the associative-reflex theory of training, the theory of motivation development and the theory of modular training. To implement the structural and methodological model, a multi-level automated system of training, control and analysis of the level of theoretical knowledge was developed, for which a certificate of state registration of the computer program No. 2017613078 dated March 10, 2017 was obtained.The structural-methodical model and the computer program provide effective work of the teacher and cadets, at the expense of the wide list of functions, ergonomics, methodical providing and application of information and communication technologies providing access of teachers and cadets to work with educational material by means of the Internet, using stationary computers, laptops, tablets and smartphones.The computer program is fully adapted to the educational process of the Academy and has a number of significant differences from other software products designed for training and control of theoretical knowledge. The main differences are in the methodology of training, testing and control aimed at encouraging students to work independently. The main motivating factor is the admission of cadets to the session in the presence of a certain percentage of self-studied issues and successful testing on the level of training.The functional structure of the computer program allows you to add new specialties or areas of training, departments, disciplines and to form a database of theoretical issues.As an example, the methodology for implementing the main function in the computer program designed to organize the control of theoretical knowledge of cadets through testing in separate disciplines and levels of training is considered.Thus, the program significantly expands the opportunities for training and control, contributes to improving the quality of cadets’ knowledge, and also creates skills for teachers and cadets to work with information and communication technologies and mobile training. Approbation of a multi-level automated system of training, monitoring and analysis of the level of theoretical knowledge has shown its high efficiency in the field of theoretical training of cadets of the Academy.